La doble carga de malnutrición y la seguridad alimentaria en la población étnica lenca hondureña. - Hernández-Santana, Adriana; Bustillo-Calidonio, Yezimiel; Vargas-Cantarero, Victor (Hacia la Promoción de la Salud)
Objective: To assess the double burden of malnutrition (DBM) and food security (FS) in the Lenca population. Method: Exploratory and descriptive study involving Lenca men and women aged 20 years or older from the municipality of Intibucá, Honduras (2023). Data on nutritional indicators were collected, and the ELCSA instrument was applied to assess FS. Statistical analysis was performed using descriptive statistics with SPSS (v 24.0)®. Results: 48.57% of women did not reach a height of 145 cm. Among men, 40.90% were overweight and 20.45% were obese; among women, 28.57% were overweight and 34.28% were obese. There were statistically significant differences in body mass index and visceral fat for the variable between sexes. 15.62% of men were affected by anemia (9.37% mild, 6.25% moderate) and 21.42% of women (12.5% mild, 8.92% moderate). Altered capillary glucose was estimated in 58.25% of women and 77.5% of men. Estimated DCM was 44% in women and 5% in men, with a prevalence of 30% in the population sample. 77.1% of households suffered from some level of food insecurity. Conclusions: The Lenca population faces food insecurity and DCM, reflected in short stature and anemia in women, as well as overweight, obesity, high body fat, and altered glucose levels in both sexes. There is a clear need for interventions to address this problem in order to prevent chronic noncommunicable diseases.